RESULTS IN TREATMENT OF THE NECK FOR STAGE III· IV CANCER OF THE TONGUE - Mitani, Hiroki; Yonekawa, Hiroyuki; Kamata, Shin-etsu (JIBI INKOKA TEMBO, 2004)
In the treatment of T3 · T4 tongue cancer, surgical therapy consisting mainly of reconstruction surgery has been performed for the primary lesion, and has definitely resulted in improvement of the control rate and survival rate compared with radium therapy. Cervical lymph node metastasis is still, however, an important prognostic factor in the treatment of tongue cancer. This article presents the results of treatment of the neck in cases of stage III · IV tongue cancer, for which primary treatment consisting mainly of surgery was performed. The subjects consisted of 201 untreated cases of squamous cell cancer of the tongue who underwent radical surgery from January 1980 to December 2000 (stage III : 129 cases, stage N : 72 cases). The results obtained were as follows. The pathological metastasis positivity rate was 67% (132/196), and the localized site showed a fixed tendency. The distribution of lymph node metastasis on the affected side broke down to Level I, 30% Level II, 48% Level III, 28% ; Level N, 11% ; Level V, 2% ; and others, 5 cases. The distribution of lymph node metastasis on the normal side was Level I, 20% ; Level II, 11% ; Level III, 19% ; Level N, 8% ; and Level V, 0%. The neck control rate was 2 years, 77.3% and 5 years, 76.1% (N = 201). The 5-year survival rate (disease specific survival rate) was 65.2% (71.1%) for stage III and 37.3% (38.7%) for stage N. With the present-day development of imaging diagnosis, preoperative diagnosis of neck lymph node metastasis has become more accurate.Therefore, the risk of clinical NO · N1 cases being found to be pathological multiple lymph node metastasis cases postoperatively is presumed to be relatively low. In recent years, neck dissection has tended to be performed only in the region requiring it in consideration of its effect on the postoperative function. In fact, superior omohyoid muscle neck dissection is performed for NO cases in many hospitals. Such a situation suggests the possibility that the range of dissection can be reduced without lowering the control results in NO cases as well as Ni cases by making an accurate preoperative assessment based on which the selection of an appropriate range of dissection can be made for each individual case. On the other hand, the neck control rate in cases of more than N2 has not yet reached a satisfactory level, and reducing the range of dissection in the cases of multiple lymph node metastasis is presumed to be difficult even today when reconstructive surgery to secure a sufficient resection safety area in the primary lesion has been established. Analysis of the cases of dissection up to Level I on the normal side, one of the causes of the neck control rate hovering at a low level, or the cases of recurrence in the non-dissection field on the normal side in N2b cases, revealed some cases in which the follow-up observations were not necessarily appropriate and neck dissection on the normal side up to distal Level III was required even among the NO cases on the normal side. From the viewpoint of improving the survival rate, raising the neck control rate further is essential, and particularly, selection of the range of dissection should be judged carefully.